Salidroside Attenuates High-Fat Diet-Induced Nonalcoholic Fatty Liver Disease via AMPK-Dependent TXNIP/NLRP3 Pathway. (22nd July 2018) - Zheng, Tao; Yang, Xiaoyan; Li, Wenjin; Wang, Qibin; Chen, Li; Wu, Dan; Bian, Fang; Xing, Shasha; Jin, Si
Abstract : Our previous studies suggested that salidroside could alleviate hepatic steatosis in type 2 diabetic C57BLKS/ Lepr db ( db/db ) mice. The aim of the present study was to evaluate the therapeutic effect of salidroside on high-fat diet- (HFD-) induced nonalcoholic fatty liver disease (NAFLD) by investigating underlying mechanisms. Mice were fed with HFD or regular diet, randomly divided into two groups, and treated with salidroside or vehicle for 8 weeks. Then, biochemical analyses and histopathological examinations were conducted in vivo and in vitro . Salidroside administration attenuated HFD-induced obesity, blood glucose variability, and hepatic lipid deposition, markedly increasing insulin sensitivity in HFD mice. In addition, salidroside suppressed oxidative stress, thioredoxin-interacting protein (TXNIP) expression, and NLRP3 inflammasome activation in the liver. In cultured hepatocytes, salidroside dose dependently regulated lipid accumulation, reactive oxygen species (ROS) generation, and NLRP3 inflammasome activation as well as improved AMP-activated protein kinase (AMPK) activity and insulin sensitivity. The inhibition of AMPK activation by inhibitor or short interfering RNA (siRNA) resulted in the suppression of the beneficial effects of salidroside in hepatocytes. Our findings demonstrated that salidroside protects against NAFLD by improving hepatic lipid metabolism and NLRP3 inflammasome activation, and these actions are related to the regulation of the oxidative stress and AMPK-dependent TXNIP/NLRP3 pathways.